Unveiling disulfidptosis-linked lncRNA signatures: insights into the immune microenvironment and drug responsiveness in oral squamous cell carcinoma - Meng, Xue; Cao, Lichao; Liu, Yantao; Wang, Sihan; Liu, Weixian; Zhang, Guangping; Guo, Siqi; Qi, Fangyu; Wang, Tingting; Xia, Yuhe; Ba, Ying; Zhang, Hezi; et al. (Frontiers in Genetics, 2025)
ObjectivesOral squamous cell carcinoma (OSCC) has a highly incidence rate and mortality rate all over the world. Hitherto, there are limited studies on survival significance between disulfidptosis-related lncRNAs (DRLs) and OSCC. Therefore, this study was conducted to investigate the potential role of these DRLs and provide some theoretical support in the clinical treatment of OSCC.MethodsOSCC-related lncRNAs and disulfidptosis-related genes (DRGs) were retrieved from public databases. Using Pearson correlation, machine learning, and expression profiling, we identified differentially expressed DRLs (DE-DRLs), developed a DE-DRLs-based risk model and independent prognostic nomogram, performed immunological and tumor microenvironment analyses to explore DE-DRLs regulatory mechanisms, predicted potential drugs for OSCC, and validated bioinformatics findings.ResultsIn this study, 9 DE-DRLs were identified that correlated with OSCC. The risk model and nomogram showed good clinical utility for assessing the likelihood of OSCC occurrence. Patients exhibiting elevated levels of eosinophils, activated natural killer (NK) cells, or naïve CD4+ T cells experienced significantly poorer overall survival (OS), and patients with high tumor mutational burden (TMB) had worse prognosis. 12 drugs were identified for OSCC treatment, such as BMS-754807_2171 and Foretinib_2040.ConclusionOur study identified 9 DE-DRLs correlated with OSCC, which will be a personalized prediction tool for prognosis and immune responses in OSCC patients.